Development of Teaching Materials for Writing Procedure Texts Using A Project Based Learning Model Based on Audio Visual Media at SMP Negeri 2 Medan - Darma, Aditya; Kaban, Benny Junior; Azis, Abdul (Education & Learning, 2024)
This examination centers around creating showing materials for composing procedural texts in view of task-based learning with general media (video) for SMP N 2 Medan. The Borg and Nerve innovative work strategy was utilized in this examination. This examination includes ten stages, beginning from the initial exploration to the eventual outcome. The examination results incorporate models of instructing materials that have been made, which are then tried for legitimacy and common sense. The examination results show that (1) the consequences of the Material Master Appraisal of the Propriety of the Substance of Showing Materials with a typical worth of (3.4) are in the great class; (2) the practicality part of showing materials with a typical worth of (3.38) is in the great class; (3) the Material Master Part viewpoint in regards to Achievability of Show with a typical worth of (3.36) is in the great class; and (4) Plan Master Evaluation Part (3.4) is in the great classification. Alluding to the approval that has been completed, procedural text showing materials utilizing the PLBL model in light of general media is plausible to be created and carried out in learning in schools..